Rancang Bangun Sistem Timbangan Digital Berbasis Internet of Things (IoT) Menggunakan ESP32 dan Load Cell untuk Mesin Beras di PT. Jaring Solusi Persada Cabang Tulungagung - Nur Akhsin Alifian Hadi; Yayak Kartika Sari; Joko Iskandar (J-INTECH ( Journal of Information and Technology), 2026)
The advancement of Internet of Things (IoT) technology in industrial sectors has driven the need for more accurate and integrated automation systems, particularly in production weighing processes. PT. Jaring Solusi Persada Tulungagung Branch required improvements in measurement accuracy, real-time data recording, and monitoring of rice milling operations. This research aims to design and develop an IoT-based digital weighing system using ESP32 and load cell to enhance operational efficiency and reduce weighing errors. The research method applied is Research and Development (R&D) using a Prototyping approach, encompassing hardware design, software development, load cell calibration, and direct system testing in the operational environment. The system utilizes the HX711 module as a signal amplifier for the load cell, with ESP32 as the main microcontroller to process weight data and transmit information in real-time via Bluetooth to a Flutter-based mobile dashboard application. Testing results indicate that the system achieved 0% error rate in weighing accuracy tests across six trials with load variations of 1–20 kg. Actuator response tests showed an average response time of 0.80 seconds with an average overshoot of 0.72% of the target weight, within acceptable tolerance for on-off control systems. IoT integration with real-time monitoring via Bluetooth successfully enabled live weight tracking and production history recording. This system demonstrates significant improvement in work efficiency, minimization of human error, and support for faster and more accurate decision-making in rice milling production